Driving the performance system. DOES research help? - Collins, D.; Cruickshank, A. (Routledge handbook of elite performance sport, 2019)
This book has predominantly taken a "hands off" approach to research, focusing rather on the challenges, interpersonal features, and ways of working across the breadth of elite performance roles, responsibilities, and contexts. Importantly however, the very nature of elite performance, the inherent and constant need to be cutting edge, makes the concept of research central to how things should work . We say should since, as several examples in this book have shown, researchers (especially academic ones) and practitioners often `enjoy ` a strained or strange relationship. Accordingly, in this chapter we explore how research can make itself more palatable and useful to elite performance. We firstly explore the inherent challenges of research in this hyper dynamic sphere, offering some methods which can help to counter them . We then consider what the researcher is trying to do, and how this viewpoint can help or hinder the application process. We then present pragmatism, a scientific approach with a rich history, as a potential `best fit` method before concluding with some next step suggestions.